Developing Performance Assessment Instruments For Local Organizations in Ecological Restoration As Part of The Cross-Cutting Capacity Development (CCCD-UNDP) Project In Indonesia - Mangku Purnomo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
Using the CCCD project as the locus of study, this paper reconstructs the empowerment process to reveal and arrange the instruments used at each empowerment stage. The performance measurement instrument was used to measure whether the organization involved in the project was related to project activities directly or indirectly. These two activities helped us compile criteria for the various organizations involved and conceptually draw the pattern of organizational relationships. Findings showed three main processes: (1) the process of identifying and selecting organizations, (2) the process of mentoring and facilitation, and (3) the process of evaluation and follow-up plan. The organizations or groups were divided into primary, secondary, and tertiary groups. Primary groups were directly related and involved in the project. Secondary groups could be involved and did not depend on funding and assistants. Tertiary groups did not need to be involved unless they had such political consequences to influence other groups. The group itself took part in decision-making about management patterns. The pattern could not be separated from the dynamics of policies, markets, and local village and supra-village politics. Based on these findings, the CCCD project confirms that a group empowerment approach must focus on the substantive aspect of achieving project goals, while the procedural aspect merely supports the administrative arrangement so objectives can be achieved more efficiently.